2023
DOI: 10.3390/su15031956
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Motivations, Abilities and Opportunities of Young Entrepreneurs to Engage in Sustainable Tourism Business in the Mountain Area

Abstract: An important driver of socio-economic development in mountain areas is sustainable tourism. Young entrepreneurs can represent a solution for the sustainable development of the mountain area. However, little is known if an opportunity or necessity drives them to engage in sustainable tourism business in the mountain area. The present study uses the motivation–ability–opportunity (MAO) framework in an effort to understand young entrepreneurs’ sustainable behavior. Semi-structured interviews with young tourism en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 115 publications
0
5
0
Order By: Relevance
“…Business success is primarily determined by competence, closely related to the entrepreneur's ability to maintain his business and achieve success. In general, successful entrepreneurs are those who have competence, namely someone who has the knowledge, skills, and individual qualities, which include attitudes, motivation, values , and behavior needed to carry out work or activities (Ivasciuc and Ispas, 2023;Jalil et al, 2023).…”
Section: Figure 2 Percentage Of Entrepreneurs Based On Last Educationmentioning
confidence: 99%
See 3 more Smart Citations
“…Business success is primarily determined by competence, closely related to the entrepreneur's ability to maintain his business and achieve success. In general, successful entrepreneurs are those who have competence, namely someone who has the knowledge, skills, and individual qualities, which include attitudes, motivation, values , and behavior needed to carry out work or activities (Ivasciuc and Ispas, 2023;Jalil et al, 2023).…”
Section: Figure 2 Percentage Of Entrepreneurs Based On Last Educationmentioning
confidence: 99%
“…Moreover, research has shown a significant link between entrepreneurial interest and success (Ardiyanti and Mora, 2019), underscoring the importance of early cultivating an entrepreneurial mindset. Additionally, business success hinges on competence, encompassing knowledge, skills, and individual qualities (Ivasciuc and Ispas, 2023;Jalil et al, 2023). Nevertheless, sustaining a business amidst increasing com-petition necessitates innovation and strong motivation (Lien et al, 2022).…”
Section: Figure 2 Percentage Of Entrepreneurs Based On Last Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Young people setting up their own companies are guided by a number of motives (Schoof 2006, 11) of an internal and external nature (entrepreneurship as an opportunity and as a life necessity) . 6 For young people, the crucial motive for thinking about their own business is often profit, necessity (escape from unemployment), the possibility of becoming independent, and creating workplaces (Bignotti and le Roux 2020, 19;Ivasciuc andIspas 2023, 1956;Palimąka and Rodzinka 2018, 100;Piecuch, Szczygieł, and Lozinsky 2019, 210) . A study on Ukrainian refugees indicates that the main motive that made them start their businesses in Poland was the need to generate income to support themselves and their families in Poland .…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%